2021
DOI: 10.1371/journal.pone.0255008
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint loadings are related to tibial torsional alignments in people with radiographic medial knee osteoarthritis

Abstract: Torsional malalignment was detected in subjects with medial knee osteoarthritis (KOA) but few studies have reported the effect of torsional deformity on knee joint loads during walking. Therefore, this study examined the relationships between lower limb torsional alignments and knee joint loads during gait in people with symptomatic medial KOA using cross-sectional study design. Lower limb alignments including tibial torsion, tibiofemoral rotation and varus/valgus alignments in standing were measured by EOS lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Loss of such mechanism and having inadequate knee flexion is harmful to knee joint, since it had been discussed that larger knee flexion at early stance phase can facilitate impact absorption and loads transmission [ 25 , 26 ]. In our previous report, we found that higher external tibial rotation was associated with greater external knee adduction moment in early stance phase in moderate knee OA, which indicated possible overload of knee joint medial compartment because of the high external tibial torsion [ 27 ]. When external tibial torsion was more likely associated with smaller knee flexion excursion, the external tibial torsion might be a potential harmful factor to knee OA mechanically.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of such mechanism and having inadequate knee flexion is harmful to knee joint, since it had been discussed that larger knee flexion at early stance phase can facilitate impact absorption and loads transmission [ 25 , 26 ]. In our previous report, we found that higher external tibial rotation was associated with greater external knee adduction moment in early stance phase in moderate knee OA, which indicated possible overload of knee joint medial compartment because of the high external tibial torsion [ 27 ]. When external tibial torsion was more likely associated with smaller knee flexion excursion, the external tibial torsion might be a potential harmful factor to knee OA mechanically.…”
Section: Discussionmentioning
confidence: 99%
“…Varus alignment may be a cause or result of gonarthrosis, which will result in the overload of medial compartment and cartilage wear [ 6 , 7 ]. If the intervention and therapy are not taken, the total knee arthroplasty (TKA) will be the only option due to the deterioration of gonarthrosis.…”
Section: Introductionmentioning
confidence: 99%